Comparison of Plasmapheresis and Molecular Adsorbent Recirculating System Efficacy in Graft Failure After Living Donor Liver Transplantation - Ince, V.; Aydin, C.; Otan, E.; Karabulut, K.; Koc, S.; Kayaalp, C.; Yilmaz, S. (Elsevier Science Inc, 2013)
Introduction. Liver transplantation may result in graft failure, requiring time and supportive treatment for regeneration of the graft. The aim of this study was to compare the laboratory parameter changes after single-session molecular adsorbent recirculating system (MARS) and plasmapheresis procedures among living donor liver transplantation patients experiencing graft failure. Patients and Method. We analyzed retrospectively the results in 45 liver transplantation patients treated with plasmapheresis and/or MARS between June 2011 and July 2012: (plasmapheresis, n = 17; MARS, n = 15; MARS + plasmapheresis, n = 13). When cadaveric donor cases (n = 11) were excluded, the remaining 34 included patients, underwent. MARS (n = 18) or plasmapheresis (n = 16) at the first session. Findings. Both groups were similar in age, sex, and body mass index features. The MARS group displayed significantly higher levels of international normalized ratio, blood urea nitrogen, and Model for End-stage Liver Disease score. The plasmapheresis cohort, displayed significantly higher levels of initial direct bilirubin and gamma glutamyl transferase (P < .05). The plasmapheresis group showed a significant decrease in GGT after treatment (P < .05). Results. An initial MARS session provided significantly greater decrease in renal function associated with graft failure after living donor liver transplantation.
9th Congress of the Turkish-Transplantation-Centers-Coordination-Association (TTCCA) -- SEP 26-29, 2012 -- Bursa, TURKEY
Keywords: Mars